Lectotypification of the Linnaean name Smilax china (Smilacaceae) - Altınordu, Fahim (Phytotaxa, 2015)
The genus Smilax Linnaeus (1753: 1028) consists of over 200 species which was widely distributed in tropical and temperate regions, especially in East Asia and North America (Qi et al. 2012, Xu et al. 2013, Qi et al. 2013). Linnaeus (1753) published 13 names under Smilax and the name Smilax china Linnaeus (1753: 1029) appears to be as yet untypified and is investigated here.